Consumer Preferences For Price And Taste In The Gultik Culinary Business At Blok M Jakarta: A Conjoint Analysis Approach - Fadli Ilyas; Dinda Aulia Ardiani; Carrisa Tsabitah Iryadh; Fathia Zahrani Assyifa; Keysa Ayumna Salsabilla; Donna Ekawaty (Jurnal Ilmiah Multidisiplin, 2025)
This study aims to explore the effect of service quality and price perception on consumer purchasing decisions at Gultik Blok M, a well-known street food destination in South Jakarta. The research adopts a quantitative approach, using a questionnaire distributed to respondents who have purchased food from the vendors at Gultik. The findings indicate that both service quality and price perception play a significant role in shaping consumer decisions. Service quality, reflected in promptness, friendliness, and cleanliness, is found to influence consumer trust and satisfaction. Meanwhile, competitive pricing and perceived value for money also encourage repeat purchases. The results support the notion that consistent quality and affordability are key factors in customer retention within the informal culinary sector. These findings have implications for micro-entrepreneurs and street vendors, suggesting the need to focus on improving service standards and maintaining fair pricing to strengthen customer loyalty in competitive urban food markets